2019
DOI: 10.1007/s00360-019-01205-z
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and thermal adaptation in semifossorial pine-voles Microtus lusitanicus and Microtus duodecimcostatus

Abstract: Rodents colonizing subterranean environments have developed several morphological, physiological and behaviour traits that promote the success of individuals in such demanding conditions.Resting metabolic rate, thermoregulation capacity and daily energy expenditure were analysed in two fossorial pine-vole species Microtus lusitanicus and M.duodecimcostatus inhabiting distinct areas of the Iberian Peninsula. Individuals were captured in locations with different habitat and soil features, allowing the comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Microtus is believed to have experienced rapid speciation and diversification, with all speciation events occurring within the past four million years [2, 3], and it has been suggested that some nominal species, such as M. pennsylvanicus , contain cryptic diversity [4]. Microtus has been an important model system across multiple biological disciplines, including studies of adaptation (e.g., [5]), infectious disease (e.g., [6]), parental care (e.g., [7]), and population dynamics (reviewed in [8]). The rapid radiation of Microtus voles has hindered systematic classification, leading to multiple taxonomic revisions and conflicting phylogenetic analyses [1, 9, 10].…”
Section: Contextmentioning
confidence: 99%
“…Microtus is believed to have experienced rapid speciation and diversification, with all speciation events occurring within the past four million years [2, 3], and it has been suggested that some nominal species, such as M. pennsylvanicus , contain cryptic diversity [4]. Microtus has been an important model system across multiple biological disciplines, including studies of adaptation (e.g., [5]), infectious disease (e.g., [6]), parental care (e.g., [7]), and population dynamics (reviewed in [8]). The rapid radiation of Microtus voles has hindered systematic classification, leading to multiple taxonomic revisions and conflicting phylogenetic analyses [1, 9, 10].…”
Section: Contextmentioning
confidence: 99%
“…This species has bigger scapulae, a larger area for muscular insertion in the femur, and more proodont upper incisors (Mathias 1990), and its tunnels have typically less openings and more surrounding soil mounds , suggesting that possibly they are better fitted for active tunneling and inhabit deeper and less ventilated burrows than M. lusitanicus. Also, M. duodecimcostatus has a lower mass-independent resting metabolic rate (Monarca et al 2019). The distribution range of both species is also largely parapatric, with M. lusitanicus mainly found in the north-northwest part of the Iberian Peninsula and M. duodecimcostatus in the south-southeast, while cooccurring within an extended band crossing the center of the Iberian Peninsula, roughly from the Lisbon area in Portugal up to the Pyrenees.…”
Section: Introductionmentioning
confidence: 96%
“…Also, M. duodecimcostatus has a lower mass‐independent resting metabolic rate (Monarca et al . 2019). The distribution range of both species is also largely parapatric, with M. lusitanicus mainly found in the north‐northwest part of the Iberian Peninsula and M. duodecimcostatus in the south‐southeast, while co‐occurring within an extended band crossing the center of the Iberian Peninsula, roughly from the Lisbon area in Portugal up to the Pyrenees.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that some nominal species, such as M. pennsylvanicus , contain cryptic diversity [ 4 ] . Microtus is an important model system across multiple biological disciplines, including studies of adaptation (e.g., [ 5 ] ), infectious disease (e.g., [ 6 ] ), parental care (e.g., [ 7 ] ), and population dynamics (reviewed in [ 8 ] ). …”
Section: Introductionmentioning
confidence: 99%